2008
DOI: 10.1007/s00428-007-0563-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of preoperative core biopsies on uPA/PAI-1 expression in breast cancer tissue

Abstract: The urokinase-type plasminogen activator (uPA) and the plasminogen activator inhibitor-1 (PAI-1) are involved in tumor invasion and metastasis as well as wound healing and inflammation. We investigated the impact of tissue injury by preoperative sampling on the level of uPA/PAI-1 in paraffin tissue of 55 breast cancer cases by immunohistochemistry. The tumor area surrounding the biopsy channel was compared with distant intact tumor tissue. uPA and PAI-1 were constantly expressed by the tumor cells. Fibroblasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…10,19,103-113. activator (uPA) complex than in intact parts of the tumor. 117 Tumor seeding in the biopsy tract is very rare, except for sarcomas. Nevertheless, surgeons are well aware of the preclinical evidence for proinvasive and prometastatic potential of wound reactions.…”
Section: Characterization and Origin Of A Myofibroblastmentioning
confidence: 99%
“…10,19,103-113. activator (uPA) complex than in intact parts of the tumor. 117 Tumor seeding in the biopsy tract is very rare, except for sarcomas. Nevertheless, surgeons are well aware of the preclinical evidence for proinvasive and prometastatic potential of wound reactions.…”
Section: Characterization and Origin Of A Myofibroblastmentioning
confidence: 99%
“…SOX-4 directly regulates expression of the Ezh2 gene that encodes the Polycomb group histone methyltransferase and epigenetically modifies expression of several EMT genes [42], [60]. (6) EMT and tumor escape, EMT allows the conversion of tumor cells toward an invasive mesenchymal phenotype allowing (7) intravasation into the circulatory system and (8) CTC chemotactic migration to the lung through the CXCR4/SDF1 axis [71], [72], [73], (9) invasion (extravasation), once in the lung the cells invade the lung tissue at the metastatic niche expressing Extra-cellular Matrix (ECM) degrading matrix metalloproteinase 9 and urokinase plasminogen activator completing the process of [74], [75], [76] (10) metastasis by successful colonization and formation of metastases.…”
Section: Discussionmentioning
confidence: 99%
“…ELISA measurements using the smaller tissue specimens correctly classified risk in 95% of the patients surveyed; however, correlation between individual uPA and PAI-1 levels in the small biopsy specimens versus the larger tissue samples was only 0.789 and 0.901, respectively. Both uPA and PAI-1 are involved in normal tissue-remodeling; consequently, pre-operative diagnostic core needle biopsies can alter their levels 39. It has recently been demonstrated that core biopsies lead to a fibroblastic inflammatory response that results in increased uPA and PAI-1 levels that can persist for up to 9 days in the surrounding tissue and even longer in the area immediately adjacent to the biopsy channel.…”
Section: Introductionmentioning
confidence: 99%